The isometric midthigh pull in basketball: An effective predictor of sprint and jump performance in male, adolescent players - Scanlan, A. T.; Wen, N.; Guy, J. H.; Elsworthy, N.; Lastella, M.; Pyne, D. B.; Conte, D.; Dalbo, V. J. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine correlations between peak force and impulse measures attained during the isometric midthigh pull (IMTP) and basketball-specific sprint and jump tests. Methods: Male, adolescent basketball players (N=24) completed a battery of basketball-specific performance tests. Testing consisted of the IMTP (absolute and normalized peak force and impulse at 100 and 250 ms); 20-m sprint (time across 5, 10, and 20 m); countermovement jump (CMJ; absolute and normalized peak force and jump height); standing long jump (distance); and repeated lateral bound (distance). Correlation and regression analyses were conducted between IMTP measures and other attributes. Results: An almost perfect correlation was evident between absolute peak force attained during the IMTP and CMJ (r=.94, R2=56%, P<.05). Moderate to very large correlations (P<.05) were observed between IMTP normalized peak force and 5-m sprint time (r=-.44, R2=19%), 10-m sprint time (r=-.45, R2=20%), absolute (r=.57, R2=33%), normalized (r=.86, R2=73%) CMJ peak force, and standing long-jump distance (r=.51, R2=26%). Moderate to very large correlations were evident between impulse measures during the IMTP and 5-m sprint time (100 ms, r=-.40, R2=16%, P>.05) and CMJ absolute peak force (100 ms, r=.73, R2=54%; 250 ms, r=.68, R2=47%; P<.05). Conclusions: The IMTP may be used to assess maximal and rapid force expression important across a range of basketball-specific movements.